PENGARUH PROFESIONALISME AUDITOR, ETIKA PROFESI, PENGALAMAN AUDITOR, DAN KOMPLEKSITAS TUGAS TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS DALAM MELAKUKAN AUDIT LAPORAN KEUANGAN - Triani, Ni Nyoman Alit (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2013)
This study aimed to determine the effect of auditor professionalism, professional ethics, auditor experience and task complexity on the level of materiality considerations. The population in this study is the auditor who worked on the public accounting firm in the area of Surabaya. Sampling technique in this study using a convenience sampling, the sample selection is based on the ease of obtaining the data. Data obtained using a questionnaire survey. Analysis tool used is multiple linear regression using SPSS.The results showed that professionalism auditor effect on consideration the level of materiality, which is indicated by value sig of 0,000; professional ethical effect on consideration the level of materiality, which is indicated by value sig of 0,008; experiences auditor effect on consideration the level of materiality, indicated by value sig of  0,000, and the complexity of the task does not effect the consideration of materiality levels, indicated by value sig of 0,21. The professionalism of the auditor, professional ethics, experience and the complexity of the task auditors jointly effect the consideration of materiality levels, indicated by the sig value of 0,000.